2015
DOI: 10.1107/s1399004715001856
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biophysical characterization of an epitope-specific engineered Fab fragment and complexation with membrane proteins: implications for co-crystallization

Abstract: Crystallization chaperones are attracting increasing interest as a route to crystal growth and structure elucidation of difficult targets such as membrane proteins. While strategies to date have typically employed protein-specific chaperones, a peptide-specific chaperone to crystallize multiple cognate peptide epitope-containing client proteins is envisioned. This would eliminate the target-specific chaperone-production step and streamline the co-crystallization process. Previously, protein engineering and dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
(71 reference statements)
0
6
1
Order By: Relevance
“…3D ). This is lower than the previously measured value of 59.8 ± 0.1 °C for the parental αEE Fab 22 , indicating that the stability of EEf15.4 is lower than that of a typical antibody generated by in vivo somatic hypermutation. Regardless, analytical size exclusion chromatography of the purified Fab peak performed after two months of storage at 4 °C showed that the proteins remained predominantly monomeric, indicting favorable storage stability (Figure S6 ).…”
Section: Resultscontrasting
confidence: 74%
“…3D ). This is lower than the previously measured value of 59.8 ± 0.1 °C for the parental αEE Fab 22 , indicating that the stability of EEf15.4 is lower than that of a typical antibody generated by in vivo somatic hypermutation. Regardless, analytical size exclusion chromatography of the purified Fab peak performed after two months of storage at 4 °C showed that the proteins remained predominantly monomeric, indicting favorable storage stability (Figure S6 ).…”
Section: Resultscontrasting
confidence: 74%
“…Monoclonal antibodies are ideal candidates as crystallization chaperones, but they have to be individually developed and screened for each target, making the strategy very costly and unpredictable. The idea of developing a portable peptide tag and anti-tag 'chaperoning' antibody has been pursued by Lieberman and colleagues (Johnson et al, 2015), but the technology has not been realized so far. As the inserted PA tag is a 'foreign' structure placed on the client protein, NZ-1 might not have a strong stabilizing effect on the conformation, as in the case of the target-specific chaperone antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Further, crystallization chaperones can also be used to induce the co-crystallization of target molecules. Crystallization chaperones are molecules that bind covalently or non-covalently to the analyte, helping it to assemble into a crystalline lattice that is then generally applied for protein analysis [ 16 , 17 ]. The Richert group discovered that tetraaryladamantanes (TAAs) are easily co-crystallized with small molecules in the form of inclusive complexes [ 18 ].…”
Section: X-ray Single-crystal Diffraction (Xrscd)mentioning
confidence: 99%